Responsibility For Public Road Parking Management For Vehicle Security and Safety in Makassar City - Nurharsya Khaer Hanafie; Rafiqur Rahman; Firman Muin; Mustaring Mustaring (Universitas Muhammadiyah Tangerang, 2022)
This study aims to determine the form of responsibility of PD Parking Makassar Raya in the event of a vehicle loss at a public roadside parking location in the city of Makassar and a description of the state of security of a public roadside parking location in the city of Makassar. To achieve this goal, the researcher used three data collection techniques, namely interviews, observation, and documentation. The data obtained were then processed through qualitative descriptive methods to clearly know how the form of responsibility of PD Parking Makassar Raya in managing public roadside parking in Makassar city and a description of the security situation of public roadside parking locations. The data used in this study are primary and secondary data. The results of this study indicate that PD Parking Makassar Raya is not responsible for the losses suffered by the vehicle owner. And the security of public roadside parking locations in Makassar city depends on CCTV cameras installed in shop buildings or buildings and the presence of parking attendants in the parking lot.